Oligodendrocyte ablation triggers central pain independently of innate or adaptive immune responses in mice - Gritsch, Simon; Lu, Jianning; Kuner, Rohini (Nature Communications, 2014)
Mechanisms underlying central neuropathic pain are poorly understood. Although glial dysfunction has been functionally linked with neuropathic pain, very little is known about modulation of pain by oligodendrocytes. Here we report that genetic ablation of oligodendrocytes rapidly triggers a pattern of sensory changes that closely resemble central neuropathic pain, which are manifest before overt demyelination. Primary oligodendrocyte loss is not associated with autoreactive T- and B-cell infiltration in the spinal cord and neither activation of microglia nor reactive astrogliosis contribute functionally to central pain evoked by ablation of oligodendrocytes. Instead, light and electron microscopic analyses reveal axonal pathology in the spinal dorsal horn and spinothalamic tract concurrent with the induction and maintenance of nociceptive hypersensitivity. These data reveal a role for oligodendrocytes in modulating pain and suggest that perturbation of oligodendrocyte functions that maintain axonal integrity can lead to central neuropathic pain independent of immune contributions.